HUBUNGAN DAYA LEDAK OTOT LENGAN DAN DAYA LEDAK OTOT TUNGKAI PADA ANGKATAN SNATCH ATLET ANGKAT BESI KOTA JAMBI - Helena Agustini Tanjung; Angel Hardi Yanto; Kevin Waldo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the relationship between arm muscle explosivepower and leg muscle explosive power with snatch performance in weightliftingathletes of Jambi City. This research employed a quantitative method with acorrelational approach. The sample consisted of 12 novice youth weightliftingathletes selected using total sampling techniques. Data were collected through theTwo-Hand Medicine Ball Put test to measure arm muscle explosive power, theVertical Jump test to measure leg muscle explosive power, and the snatch lift testto assess snatch performance. Data were analyzed using descriptive statistics andSpearman Rank correlation analysis. The results showed that arm muscleexplosive power had a positive relationship with snatch performance with acorrelation coefficient of 0.311, while leg muscle explosive power had a positiverelationship with snatch performance with a correlation coefficient of 0.382.Simultaneously, arm and leg muscle explosive power demonstrated a positiverelationship with snatch performance, indicated by a multiple correlation coefficientof 0.493. These findings suggest that greater explosive power contributes toimproved snatch performance among weightlifting athletes. Therefore, coachesare encouraged to design training programs that focus on enhancing both arm andleg muscle explosive power to optimize athletes’ performance in snatch lifting.